Analysis of The Effectiveness of Project-Based Learning Models on Students' Creativity in Physics Learning: A Systematic Literature Review - Maria Anastasia Da Lopez; Baiq Anisya Nelahi Purnadya (Indonesian, 2023)
Creative thinking is an essential 21st-century competency. This Systematic Literature Review (SLR) using a descriptive method based on PRISMA 2020 guidelines aims to analyze the effectiveness of Project Based Learning (PjBL) on students' creativity in physics learning. Literature was retrieved via Google Scholar using Publish or Perish software covering 2014–2023 publications. Selection results identified 15 articles meeting inclusion criteria. Synthesis reveals that PjBL consistently exerts a high-category, significant positive effect, evidenced by an effect size reaching 1.308. Fluency showed the highest improvement, whereas originality remains the greatest challenge. PjBL achieves optimal effectiveness when synergized with STEM approaches and digital media (such as PhET Simulation and YouTube) as visual scaffolding for abstract concepts. In conclusion, PjBL effectively enhances motivation and creativity through real-product creation. This study recommends developing multimodal approaches within PjBL to address students' low originality scores identified across a decade of literature.